1992
DOI: 10.1007/bf02013498
|View full text |Cite
|
Sign up to set email alerts
|

Choroid plexus cysts: A normal finding on ultrasound

Abstract: Within a period of 2.5 years, cystic structures in the choroid plexus were encountered at cerebral sonography in 70 neonates and babies (45 male, 25 female; 18 premature babies). Their prevalence in patients examined during the first 4 weeks of life (n = 55) was 3%. The size of the cysts ranged from 1-4 and, rarely, up to 7 mm. They were mostly solitary and unilateral. Follow-up sonograms over periods up to 13 months showed that most of the cysts persisted unchanged. A few disappeared (n = 7), while distinct i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 10 publications
0
15
0
1
Order By: Relevance
“…There is an association with chromosomal abnormalities such as trisomy 18 if the cysts are greater than 1 cm, bilateral and if other structural abnormalities are present,33 and some reports associate CPC with cytomegalovirus 24. The largest study of CPC seen on postnatal cUS in 70 preterm and term infants (age range 1 day to 1 year) reported an incidence of 3%;34 in our cohort 19.6% had CPC of which 10% were isolated, the remaining cases had abnormal tissue echogenicities but not structural abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…There is an association with chromosomal abnormalities such as trisomy 18 if the cysts are greater than 1 cm, bilateral and if other structural abnormalities are present,33 and some reports associate CPC with cytomegalovirus 24. The largest study of CPC seen on postnatal cUS in 70 preterm and term infants (age range 1 day to 1 year) reported an incidence of 3%;34 in our cohort 19.6% had CPC of which 10% were isolated, the remaining cases had abnormal tissue echogenicities but not structural abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…The largest report of choroid plexus cysts on postnatal sonography was done by Riebel et al 3 They reported on 70 neonates. The cysts were usually situated in the dorsal part of the choroid plexus.…”
Section: Discussionmentioning
confidence: 99%
“…The features of benign, choroid plexus cysts which dis tinguish them from pathological cysts such as those found in Aicardi syndrome are their confinement to the glomus [14], smaller size-usually 1-4 mm in size and rarely up to 7 mm [15]-and usual stability in size or complete disap pearance over time [ 15].…”
Section: Discussionmentioning
confidence: 99%